Notions of justice held by stakeholders of the Newfoundland fishery. (December 2015) - Kahmann, Birte; Stumpf, Klara Helene; Baumgärtner, Stefan
Abstract: Justice is an important and contested issue in the governance of fish stocks threatened by overexploitation. This study identifies the notions of justice held by stakeholders of the fishery in Newfoundland, Canada, using qualitative interviews, and interprets these notions in light of established justice theories. The interviews are analysed using inductive and deductive coding. A central result is that inshore fishers are seen as the main claim holders, with a claim to participate and be listened to, and the opportunity to make a living from the fishery. Moreover, rules play an important role in the justice notions of the interview partners, and their justice notions are clearly plural. The stakeholder notions of justice in the Newfoundland fishery resonate with the emphasis on recognition, participation and distribution as important aspects of justice within the environmental justice approach [59-61] (Schlosberg 2004, 2007, 2013). Highlights: This study is concerned with justice in the Newfoundland fishery. Qualitative interviews are used to study stakeholder notions of justice. The results are structured according to key conceptual elements of justice. Recognition, participation and distribution are important in this context.